The Use of Project-Based Learning on Early Childhood Financial Literacy Skills - Kalsum, Syahrini; Rusmayadi, Rusmayadi; Musi, Muhammad Akil; Halik, Abdul (International Journal of Multidisciplinary Approach Research and Science, 2025)
Literacy is a set of individual abilities and skills in reading, writing, speaking, counting, and problem-solving at a certain level of expertise required in everyday life. Basic literacy consists of 6 things, namely language literacy, numerization literacy, science literacy, digital literacy, financial literacy, and cultural/civic literacy. Financial literacy is education on how to manage finances wisely as needed. Financial literacy education is given to children from an early age with the hope that children are used to managing finances well so that they can be free from financial problems in the future and can achieve their welfare This research is an experimental research that aims to find out whether there is an influence of project-based learning on early childhood financial literacy skills. The data analysis technique is analyzed using the paired sample t-test technique. Based on the paired sample test results, a t-value of -16.412 was obtained with a significance value of 0.001 < 0.05. It can be concluded that project-based learning has a significant effect on early childhood financial literacy skills.